2020
DOI: 10.1093/ve/veaa049
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence and evolution of highly pathogenic porcine epidemic diarrhea virus by natural recombination of a low pathogenic vaccine isolate and a highly pathogenic strain in the spike gene

Abstract: Abstract Outbreaks of a new variant of porcine epidemic diarrhea virus (PEDV) at the end of 2010 have raised interest in the mutation and recombination of PEDV. A PEDV strain (CN/Liaoning25/2018) isolated from a clinical outbreak of piglet diarrhea contained a 49 bp deletion in the ORF3 gene. This deletion is considered a genetic characteristic of low pathogenic attenuated vaccine strains. However, CN/Liaoning25/2018 was highly pathogenic. Complete genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The development of an effective and safe vaccine against SARS-CoV-2 is of paramount importance. Although there are no licensed vaccines against CoVs in humans so far, the various issues (lack of complete protection, short duration of immunity, correlates of protection against CoVs, emergence of multiple serotypes/subtypes including virulent recombinants between vaccine and field strains, and/or ADE enhanced disease) observed with the veterinary CoV vaccines should be taken into consideration while devising immunization strategies against SARS-CoV-2 [ 17 , 18 , 22 , 30 , 32 , 33 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of an effective and safe vaccine against SARS-CoV-2 is of paramount importance. Although there are no licensed vaccines against CoVs in humans so far, the various issues (lack of complete protection, short duration of immunity, correlates of protection against CoVs, emergence of multiple serotypes/subtypes including virulent recombinants between vaccine and field strains, and/or ADE enhanced disease) observed with the veterinary CoV vaccines should be taken into consideration while devising immunization strategies against SARS-CoV-2 [ 17 , 18 , 22 , 30 , 32 , 33 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the currently licensed animal CoV vaccines appeared to reduce mortality/viral shedding, none seem to offer complete protection [ 33 ]. Other concerns associated with the animal CoV vaccines included a relatively short duration of protective immunity, lack of a clear understanding of the correlates of protection against CoVs, emergence of multiple serotypes/subtypes that influence vaccine efficacy, and/or ADE enhanced disease [ 14 , 17 , 18 , 22 , 30 , 32 , 33 , 254 , 255 ].…”
Section: Prophylaxis Against Sars-cov-2 and The Animal Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…This recombination occurred not only in structural protein-coding region (S and N genes) but also in non-structural protein-coding region (pp1a gene and ORF3) [ 48 ]. PEDV TCN/Liaoning25/2018 (GenBank: MK796238.1) was another natural recombinant strain that contains the S gene from the highly pathogenic CH/GDZQ/2014 strain (GenBank:KM242131.1) and the remaining genomic regions from the low pathogenic vaccine isolate SQ2014 (GenBank: KP728470.1) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The only accessory protein ORF3 has ion channel activity ( Wang et al, 2012 ), and was found beneficial to virus proliferation ( Wang et al, 2012 ; Ye et al, 2015 ; Si et al, 2020 ). Phylogenetic analysis showed that PEDV could be divided into two genotypes (G1 and G2) and five subgenotypes (G1a, G1b, G2a, G2b, and G2c) based on complete sequence of S gene ( Fan et al, 2017 ; Hsueh et al, 2020 ; Wang H. et al, 2020 ; Wang X.W. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%